Death's daughter - Barnes, S. A. (Barnes, S. A. Children of the old ones, 2026)
After a lifetime of chaos, Jocasta has finally found her home with good friends, great classes, even a messy situationship with her former TA--a normal life. Well, as normal a life as the only child of Death can have. She's always refused to embrace her father's legacy. Instead of taking lives, she feeds on her classmates' disappointments, failures, and rejections. Finals week has her feasting, and all is good. Until Death ruins her life. Again. Without warning, Death names Jocasta as his sole successor, making her a powerful ally ... and a massive target. Devon, a descendant of Lust, claims to want to help her--for a price. Jo will do anything to protect the people she loves and the life she's worked so hard for. Even if it means becoming a monster.